Late Neogene Inversion and Subduction Initiation in the SE Sundaland: Insights from Seismic Observation of Regional Reverse and Back-thrust Faults from East Java to Wetar, Indonesia - RM Iman Argakoesoemah (Berita Sedimentologi, 2026)
The Late Neogene tectonics in East Java region have led to significant geological deformations. For example, the regional structures of the Cepu-to-Central High inversion and Baribis-to-Wetar back-thrust fault are the result of the Australian Oceanic Plate subducting beneath southeast of the Cretaceous Sundaland in an orthogonal direction. These inversion structures and back-thrust faults are prominent and continuously active in onshore East Java in the west and further east. The west-east regional structure of the Cepu-to-Central High inverted graben remains attractive for hydrocarbon exploration and development in Indonesia. The region has been one of the focal points in the East Java Basin and has two well-known proven petroleum systems. Oil and gas fields have been continuously discovered until very recently in both the Eocene-to-Miocene thermogenic and Pliocene-to-Pleistocene biogenic plays. Hydrocarbon plays in the region have been significantly improved and added since the first oil was discovered by the Dutch in pre-World War II in-line with the use of new exploration concepts and techniques, as well as drilling technology. The extent of the Baribis-to-Wetar back-thrust fault was seismically defined in onshore East Java towards offshore Wetar. The 2D seismic interpretation indicated that the segment of the Kendeng-Bali back-thrust fault has a low-angle blind-thrust fault system. Towards the east, in the Lombok-Flores-Wetar segment, the blind-thrust fault has developed its thrust style, and the fault thrust-tip line has broken all the way to the sea floor. At this point, the beginning of Flores intra-oceanic subduction initiation might have occurred in the post-Early Pleistocene to form a Flores nascent trench. Along this back-thrust segment, the central to east Sunda Arc is seismically very active and devastating.